Three new species of the subfamily Nossidiinae (Coleoptera: Ptiliidae) from South Korea - Jang, Taeyoung; Sörensson, Mikael; Park, Jong-Seok (Zootaxa, 2023)
The subfamily Nossidiinae was established in 2019 and is comprised of five genera including one fossil genus. Among them, Nossidium Erichson and Sindosium Johnson share many morphological similarities. To this point, two extant Nossidium-species, N. flachi Ganglbauer and N. pilosellum (Marsham) have been recorded in the Palaearctic realm. In this paper, we describe three new species, Nossidium koreanum sp. nov., Sindosium longifilum sp. nov. and S. chungbukicum sp. nov. from South Korea. These are the first Nossidiinae species described from Korea, as well as the first Palaearctic record of the genus Sindosium.